Kontribusi Gratitude Dan Anxiety Terhadap Spiritual Well-Being Pada Orang Tua Anak Berkebutuhan Khusus - Asti Meiza; Diah Puspasari; N Kardinah (HUMANITAS: Indonesian Psychological Journal, 2018)
This research aims to determine the effect gratitude and anxiety with spiritual well-being in the parents of children with special needs. Research carried out by the quantitative method with 100 subjects. Data analysis was performed using multiple linear regression model where Gratitude and Anxiety as independent variables and Spiritual Well Being (SWB) as the dependent variable. Results indicate a positive influence between Gratitude and Anxiety to SWB. The majority of the subjects had state anxiety, so they can manage and control the emotions that give a positive effect on SWB.